NASIONALISME AJENGAN RUHIAT (Gagasan dan Praksis Nasionalisme Seorang Ulama) - Faisal Fadhila Hatami Faisal Fadhila Hatami (Program Magister Ilmu Politik, Universitas Diponegoro, 2016)
Nationalism is the main issue before independence. Therefore, the nationalismactivators of Indonesia emerged from the various area in West Java, especially Tasikmalaya, one of them was Ajengan Ruhiat who an Ulama nationalism activator. That his name is not as popular as Kiai Haji Zaenal Mustafa, a national hero form the same area. The goal of this article is to how the idea and the nationalism praxis before independence and how the response of Ajengan Ruhiat to the socio-politics condition. As a result, Ajengan Ruhiat had a moderat nationalism view. Ajengan Ruhiat more concerned to the islamification of the public than the islamification of the country. According his actions in establishing Pesantren Cipasung (Cipasung Islamic Boarding School), in the time context, can be showed how the nationalism progressive of Ajengan Ruhiat, because Pesantren Cipasung is included as a pioneer of public school establishment in West Java.